THE ANTIMICROBIAL ACTIVITY ASSAY OF LEAF EXTRACTS OF MORINGA (Moringa Oleiferalam) - Ansori (Journal of Holistic and Traditional Medicine, 2020)
Plants are a source of various types of chemical compounds that have medicinal properties. The use of plants as medicine is alegacy from our ancestors that has been used since time immemorial and has been widely used for a long period of time almost all over the world. Research on natural ingredients itself has been widely researched in Indonesia. This is related to the content ofactive ingredients as a result of secondary metabolism in plants which can provide many benefits, one of which is found in Moringa plants are efficacious as anti-cancer, anti-bacterial, hypotensive, inhibiting the activity of bacteria and fungi. The chemical content contained in it is rich in vitamin A and vitamin C, glucosionate and isothiosinate compounds.